European integration and domestic regions: A numerical simulation analysis - Arne Melchior (Center for Social and Economic Research (CASE), 2009)
Does European economic integration create more inequality between domestic regions, or is the opposite true? We show that a general answer to this question does not exist, and that the outcome depends on the liberalisation scenario. In order to examine the impact of European and international integration on the regions, the paper develops a numerical simulation model with nine countries and 90 regions. Eastward extension of European integration is beneficial for old as well as new member countries, but within countries the impact varies across regions. Reduction in distance-related trade costs is particularly good for the European peripheries. Each liberalisation scenario has a distinct impact on the spatial income distribution, and there is no general rule telling that integration causes more or less agglomeration.
Keywords: F12; F15; R12; O18; 330; Regional inequality; international trade; European integration; Europäische Integration; Räumliche Verteilung; Wirtschaftliche Konvergenz; Regionalentwicklung; Theorie; Europa